2023
DOI: 10.1126/sciadv.adg9601
|View full text |Cite
|
Sign up to set email alerts
|

Transformable nano-antibiotics for mechanotherapy and immune activation against drug-resistant Gram-negative bacteria

Rong Sheng Li,
Jiahui Liu,
Cong Wen
et al.

Abstract: The dearth of antibiotic candidates against Gram-negative bacteria and the rise of antibiotic resistance create a global health concern. The challenge lies in the unique Gram-negative bacterial outer membrane that provides the impermeable barrier for antibiotics and sequesters antigen presentation. We designed a transformable nano-antibiotics (TNA) that can transform from nontoxic nanoparticles to bactericidal nanofibrils with reasonable rigidity (Young’s modulus, 21.6 ± 5.9 MPa) after targeting β-barrel assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…coli and Gram-positive S. aureus, place an enormous burden on public health and the social economy owing to their high invasiveness and ubiquity in daily life. , In view of the excellent plasmonic catalysis and localized heating of the FeCG nanozyme, we first investigated the antibacterial activity of plasmonic FeCG against E. coli and S.…”
Section: Resultsmentioning
confidence: 99%
“…coli and Gram-positive S. aureus, place an enormous burden on public health and the social economy owing to their high invasiveness and ubiquity in daily life. , In view of the excellent plasmonic catalysis and localized heating of the FeCG nanozyme, we first investigated the antibacterial activity of plasmonic FeCG against E. coli and S.…”
Section: Resultsmentioning
confidence: 99%
“…However, the poor penetration of the nanomaterials into biofilm greatly limited the efficiency of combating BAIs. Various strategies have been developed to enhance the permeability of nanostructures, including controlling the size and shape, , polymer-targeted modification, matrix component-degrading enzyme decoration, liposome encapsulation, and polypeptide modification. Nanoparticles with sharp shapes were more likely to destroy the substrate structure of biofilm than blunt particles. , Recently, Qian et al synthesized a magnetic zeolitic imidazolate framework (ZIF) with a flower-like clustered structure for combating biofilm infections via combining the photothermal with catalytic properties, which demonstrated that the flower-like structure could destroy the local biofilm structure to increase the penetration . In addition, the sharp-shaped nanostructures equipped with magnetic nanoparticles provided enormous potential for biofilm destruction. Magnetic nanoparticles tunneled channels into the biofilm under an alternating magnetic field (AMF), thus improving the permeability of the antibacterial agent.…”
Section: Introductionmentioning
confidence: 99%
“…35−38 Nanoparticles with sharp shapes were more likely to destroy the substrate structure of biofilm than blunt particles. 39,40 Recently, Qian et al synthesized a magnetic zeolitic imidazolate framework (ZIF) with a flower-like clustered structure for combating biofilm infections via combining the photothermal with catalytic properties, which demonstrated that the flowerlike structure could destroy the local biofilm structure to increase the penetration. 41 In addition, the sharp-shaped nanostructures equipped with magnetic nanoparticles provided enormous potential for biofilm destruction.…”
Section: Introductionmentioning
confidence: 99%
“…However, their efficacy is often suboptimal because of insufficient entry into bacteria and the occurrence of drug resistance (10)(11)(12)(13)(14). For instance, Pseudomonas aeruginosa, a causative pathogen of exacerbations in patients with severe COPD, has a low-permeability outer membrane, which limits the penetration of antibiotics into the cells (15,16). Antimicrobial peptides (AMPs) and AMP mimics, which typically consist of cationic and hydrophobic amino acid residues, serve as important alternatives to antibiotics and can kill bacteria by directly destabilizing/ disrupting their membranes (17).…”
Section: Introductionmentioning
confidence: 99%